PENGARUH KARAKTERISTIK, PENGETAHUAN, SIKAP DAN MOTIVASI KADER KESEHATAN TERHADAP PENEMUAN SUSPEK TB DI KOTA BENGKULU TAHUN 2024 - Hariadi, Efrizon; Hariadi, Sahran; Lestari, Widia (Politeknik Kesehatan Kemenkes Bengkulu, 2025)
Background. Tuberculosis (TB) is still a health problem, especially in developing countries including Indonesia. TB is the third largest cause of death after cardiovascular and respiratory diseases, and is the number one disease in the infectious disease group. WHO targets the achievement rate of new TB case detection (Case Detection Rate/CDR) of 70%. The CDR achievement rate in Bengkulu Province is 42% and 28% TB in children. This achievement is still very low when compared to the target of the Pulmonary TB control program. The discovery of TB sufferers in the DOTS (Directly Observed Treatment Shortcourse) strategy is carried out passively (passive case finding), namely the screening of TB suspects is carried out only on sufferers who visit health service facilities, especially health centers. An alternative to finding TB cases is Active Case Finding, namely capturing TB suspects by involving the participation of the community including cadres to increase the coverage rate of TB detection, examination and treatment. Objective. This study aims to determine the effect of characteristics, knowledge, attitudes and motivation of health cadres on the discovery of TB suspects in Bengkulu City. Method. Cross-sectional research design. The sample of the study was health cadres. Data analysis using the chi square test. Research results. The test results obtained p value > 0.05 so that there is no difference in the level of knowledge, attitude and motivation of health cadres between health centers with low TB suspect detection and health centers with high TB ​​suspect detection. The test results obtained p value > 0.25 so that the variables of gender, occupation, age and work experience have no relationship with the discovery of TB suspects. The test results obtained p value 0.159 means p value <0.25 so that the education level variable has a relationship with the discovery of TB suspects. Conclusion. Most of the coverage of TB suspect detection is still low in Bengkulu City at 87%. The variable of education level is related to the detection of TB suspects in Bengkulu City. The variables of knowledge level, attitude, motivation, gender, type of work, age, and work experience are not related to the detection of TB suspects.